Growth and optical properties of thulia-doped cubic yttria stabilized zirconia single crystals. Issue 13 (September 2019) - Xu, Shoulei; Tan, Xiaojun; Liu, Fenhong; Zhang, Lei; Huang, Yuyang; Goodman, Bernard Albert; Deng, Wen
Abstract: Single crystals of yttria stabilized zirconia (YSZ) doped with different thulia (Tm2 O3 ) contents (0.2–3.0 mol%) (abbreviated to Tm2 O3 : YSZ) were grown by the optical floating zone method. The crystals were transparent and inclusion free. These samples were then analyzed by X-ray diffraction (XRD), thermogravimetric-differential thermal analysis (TG-DSC), and Raman spectroscopy, and their optical properties were determined with Ultraviolet–visible (UV–Vis) and Photoluminescence spectroscopy (PL). The Tm2 O3 : YSZ single crystals were in the cubic phase, and the lattice parameters first increased and then decreased with increasing Tm2 O3 content. The absorption spectra showed four peaks at around 356 nm ( 3 H 6 → 1 D 2 ), 460.5 nm ( 3 H 6 → 1 G 4 ), 678.5 nm ( 3 H 6 → 3 F 2, 3 ) and 784 nm ( 3 H 6 → 3 H 4 ) in the visible region, and the optical bandgap energy increased with increasing Tm2 O3 content, as a result of the Moss-Burstein effect. Measurements of PL spectra indicated a strong blue emission peak at 458 nm ( 1 D 2 → 3 F 4 ), and three weak emission peaks at 487 nm ( 1 G 4 → 3 H 6 ), 497 nm ( 1 D 2 → 3 H 5 ), and 656.5 nm ( 1 G 4 → 3 F 4 ) when the crystals were excited by light with a wavelength of 356 nm. The intensities of the emission peaks were strongly affected by the Tm2 O3 content of the YSZ single crystals; the intensity increased with Tm2 O3 content at low doping levels, reached the maximum at 0.5 mol% Tm2 O3, then decreased with further increase in Tm2 O3 content due to the concentration quenching effect. Additionally, the color changed from blue to cyan as the Tm2 O3 content was increased. Overall, this work demonstrates that the cubic YSZ single crystal is a suitable host material for solid state luminescence.